2019
DOI: 10.1051/epjconf/201921407014
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a heterogeneous compute resource in the ATLAS workflow

Abstract: With the ever-growing amount of data collected with the experiments at the Large Hadron Collider (LHC), the need for computing resources that can handle the analysis of this data is also rapidly increasing. This increase will even be amplified after upgrading to the High Luminosity LHC [1]. High-Performance Computing (HPC) and other cluster computing resources provided by universities can be useful supplements to the resources dedicated to the experiment as part of the Worldwide LHC Computing Grid (WLCG) for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…To provide theoretical guidelines for experimental analysis and simplified template cross sections (STXS), we adopt the same jet definition as in ATLAS measurements [39,40] and study differential observables using fiducial bins suggested by STXS stage 1.1 [41]. We study on-shell Higgs bosons of m H = 125 GeV, produced in the VBF, VH, and ggF channel with a center-of-mass energy of 13 TeV.…”
Section: Jhep11(2021)108 2 Theoretical Inputs and Computational Toolsmentioning
confidence: 99%
“…To provide theoretical guidelines for experimental analysis and simplified template cross sections (STXS), we adopt the same jet definition as in ATLAS measurements [39,40] and study differential observables using fiducial bins suggested by STXS stage 1.1 [41]. We study on-shell Higgs bosons of m H = 125 GeV, produced in the VBF, VH, and ggF channel with a center-of-mass energy of 13 TeV.…”
Section: Jhep11(2021)108 2 Theoretical Inputs and Computational Toolsmentioning
confidence: 99%